2006
DOI: 10.1055/s-2006-926404
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Cyclopropene Chemistry

Abstract: In this review, a brief outline of synthetic methods toward cyclopropenes is provided. Main emphasis is placed on transformations of cyclopropenes proceeding with preservation of the ring, with a spotlight on recent developments in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…We have recently shown that “unstable” cyclopropenes from a broad spectrum of vinyldiazo compounds can be generated photochemically in the presence of 1,3-dipoles to produce [3 + 2]-cycloaddition products in generally high yields and diastereocontrol. 8 The propensity of stable cyclopropenes to undergo [4 + 2]-cycloaddition reactions is well known, 9 but these transformations have been limited to cyclopropenes that do not undergo the ene reaction. This manuscript reports how previously inaccessible cyclopropene intermediates from diverse vinyldiazoacetates can be conveniently generated photolytically to undergo [4 + 2]-cycloaddition reactions with α-halohydrazones, cyclopentadiene, and furan for the synthesis of heterocyclic and bicyclic compounds ( Scheme 1B ).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that “unstable” cyclopropenes from a broad spectrum of vinyldiazo compounds can be generated photochemically in the presence of 1,3-dipoles to produce [3 + 2]-cycloaddition products in generally high yields and diastereocontrol. 8 The propensity of stable cyclopropenes to undergo [4 + 2]-cycloaddition reactions is well known, 9 but these transformations have been limited to cyclopropenes that do not undergo the ene reaction. This manuscript reports how previously inaccessible cyclopropene intermediates from diverse vinyldiazoacetates can be conveniently generated photolytically to undergo [4 + 2]-cycloaddition reactions with α-halohydrazones, cyclopentadiene, and furan for the synthesis of heterocyclic and bicyclic compounds ( Scheme 1B ).…”
Section: Introductionmentioning
confidence: 99%
“…However, compared with allylation, so far there are no documented examples on the use of nucleophiles and propargylic electrophiles in three-component reactions of diazo compounds . The potential challenges in developing such a protocol are (1) the greater complexity in achieving regioselective and chemoselective propargylic substitution than that of allylic substitution owing to the product diversity; (2) the competitive direct propargylic substitutions between the nucleophilic substrates and propargylic substrates; and (3) possible side reaction such as dirhodium­(II)-catalyzed cyclopropenation reaction between diazo compounds and triple bond of propargylic substrates …”
Section: Introductionmentioning
confidence: 99%
“…74 The potential challenges in developing such a protocol are (1) the greater complexity in achieving regioselective and chemoselective propargylic substitution than that of allylic substitution owing to the product diversity; 1−8 (2) the competitive direct propargylic substitutions between the nucleophilic substrates and propargylic substrates; and (3) possible side reaction such as dirhodium(II)-catalyzed cyclopropenation reaction between diazo compounds and triple bond of propargylic substrates. 75 The combined use of two or even more metal catalysts to construct new C−C and C−X bonds in a single operation has attracted widespread attention since novel reactivity and selectivity might be achieved together with a bonus of simplified workup procedures. 76−82 In particular, bimetallic and tandem catalysis has emerged as an efficient and reliable method to enable a series of new transformations, 83−90 which might offer potential opportunities to achieve the difunctionalization of diazo compounds together with propargylation in MCRs.…”
Section: Introductionmentioning
confidence: 99%
“…Unsaturated three-membered ring systems have been the subject of numerous studies because of their unique electronic structures and properties. As diverse synthons in synthetic chemistry, cyclopropenes have been extensively studied . In the late 1990s, Sekiguchi and Power independently reported the first synthesis of cyclotrigermenes and a cyclotrigermene radical .…”
mentioning
confidence: 99%